Gradivo o ljudski medicini v zapisih terenskih ekip Slovenskega etnografskega muzeja - Sosič, Barbara (Etnolog. Nova vrsta (Ljubljana), 2000)
The article brings a survey of the material on folk medicine, which was collected by the field teams of the Slovene Ethnographic Museum and their collaborators between 1948 and 1984. Most of it originates from Dolenjska, Primorska, Štajerska, and Notranjska. The article introduces the reader to the hardly known material on folk medicine, which is kept by the Documentation Department of the Slovene Ethnographic Museum, and which is largely in the form of type-written copies of field notes. The following data are recorded: year, author, place(s) of notes as well as the diseases and treatment of people and animals with home-made natural substances, which were used in the countryside until the mid 20th century.
Keywords: ethnology; etnologija; ljudska medicina; Slovenci; Slovenes; Slovenski etnografski muzej; terenske ekipe